2016
DOI: 10.1038/srep37363
|View full text |Cite
|
Sign up to set email alerts
|

Zeta potential in oil-water-carbonate systems and its impact on oil recovery during controlled salinity water-flooding

Abstract: Laboratory experiments and field trials have shown that oil recovery from carbonate reservoirs can be increased by modifying the brine composition injected during recovery in a process termed controlled salinity water-flooding (CSW). However, CSW remains poorly understood and there is no method to predict the optimum CSW composition. This work demonstrates for the first time that improved oil recovery (IOR) during CSW is strongly correlated to changes in zeta potential at both the mineral-water and oil-water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
193
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(219 citation statements)
references
References 62 publications
15
193
3
Order By: Relevance
“…In this mechanism, negatively charged nanoparticles diffuse around oil droplets lodged on the glass surface. Recalling that the water-oil interface beneath the oil droplet is of negative charge, except at the high pH and ionic strength relevant to the formation brines (Jackson et al 2016) and/or in highly acidic crude oil (Buckley 1999), as a result, repulsion between the interfaces leads to detachment of oil droplets from the surface by nanoparticles, and consequently, wettability changes the glass surface from oil wet toward water wet.…”
Section: The Effect Of Nanoparticle Concentration In Deionized Water mentioning
confidence: 99%
“…In this mechanism, negatively charged nanoparticles diffuse around oil droplets lodged on the glass surface. Recalling that the water-oil interface beneath the oil droplet is of negative charge, except at the high pH and ionic strength relevant to the formation brines (Jackson et al 2016) and/or in highly acidic crude oil (Buckley 1999), as a result, repulsion between the interfaces leads to detachment of oil droplets from the surface by nanoparticles, and consequently, wettability changes the glass surface from oil wet toward water wet.…”
Section: The Effect Of Nanoparticle Concentration In Deionized Water mentioning
confidence: 99%
“…Yousef, et al [183] demonstrated that ζ-potential of the rock-brine interface decreases as the brine salinity decreases and suggested that Ca 2+ ions leave the rock surface in form of mineral dissolution and enter the brine solution to re-establish chemical equilibrium. Jackson, et al [187] correlated improved oil recovery to ζpotential of rock-brine and oil-brine interfaces using a reservoir limestone core, different crude oil and brine solution. The authors concluded that the potential for improved oil recovery by low saline brine injection is increased when both interfaces possess the same polarity (ζ-potential sign), such that the electrostatic repulsive force generated between the interfaces stabilizes the water film on the rock surface.…”
Section: Sandstone Rocksmentioning
confidence: 99%
“…However, the root causes of this wettability alteration effect, which takes place at the pore-level, remain poorly understood especially for carbonates [6]. This lack of fundamental understanding of root causes of wettability alteration has resulted in conflicting studies, where some studies have observed an increase in oil recovery while other cases have not shown an increment in oil recovery [7]. Various pore-scale mechanisms have been proposed to delineate the wettability alteration process in carbonates.…”
Section: Introductionmentioning
confidence: 99%